The effective promotional tools on halal food certification among Small-Medium Enterprise (SMEs): A case study at Ayer Keroh by Sirim Berhad / Norida Abu Bakar - Abu Bakar, Norida (Faculty of Business and Management, 2005)
The primary objective of the promotion is to communicate with customers with respect to product offerings. Promotion has a key role in determining profitability and market success and is one of the key "Four Ps" of the marketing mix. The tools that can be employed in the promotional mix include: advertising; direct marketing; sales promotion; public relations and publicity; personal selling and sponsorship. An organization can use a variety of different promotional tools to communicate with its potential customers. Therefore, the aim of this study is to identify the promotion mix that can effectively promote the Halal Food Certification among the SMEs. Besides that, this study also wants to identify the level of awareness of Halal Food Certification among the SMEs. The study focuses only to the SMEs company in the area of Ayer Keroh Indutrial Estate using the full census method.